The Relationship Between Self-Concept and Aggressive Behavior in Junior High School Students: Hubungan Antara Konsep Diri Dengan Perilaku Agresif Pada Peserta Didik di Sekolah Menengah Pertama - Ananda Astriani Ramadhanti; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2021)
This research is motivated by the phenomenon of aggressive behavior in junior high school students. One of the factors that influence aggressive behavior is self-concept. This study aims to determine the relationship between self-concept and aggressive behavior in students at Private Junior High School X Tanggulangin. This research is a type of quantitative research with a correlational approach. The variables contained in this study are self-concept as the independent variable and aggressive behavior as the dependent variable. This research was conducted at the Private Junior High School X Tanggulangin with a total sample of 143 and was taken with a saturated sampling technique. Data collection techniques in this study used two Likert model psychological scales, namely the self-concept scale and the aggressive behavior scale. The hypothesis in this study is that there is a negative relationship between self-concept and aggressive behavior in students at SMP Swasta X Tanggulangin. Analysis of the data used is analysis with Pearson Product Moment correlation technique using SPSS 18 for windows program. The results of the data analysis of this study showed a correlation coefficient of -0.275 with a significance of 0.000. So there is a negative relationship between self-concept and aggressive behavior in students at Private Junior High School X Tanggulangin and the initial hypothesis proposed by the researcher is acceptable. The effective contribution of self-concept to aggressive behavior in this study was 7.5%. Keywords: Self-concept, Aggressive Behavior, Students of Private Junior High School X Tanggulangin